Construction, Corruption, and Developing Countries - Kenny, Charles (World Bank, Washington, DC, 2012)
The construction industry accounts for about one-third of gross capital formation. Governments have major roles as clients, regulators, and owners of construction companies. The industry is consistently ranked as one of the most corrupt: large payments to gain or alter contracts and circumvent regulations are common. The impact of corruption goes beyond bribe payments to poor quality construction of infrastructure with low economic returns alongside low funding for maintenance-and this is where the major impact of corruption is felt. Regulation of the sector is necessary, but simplicity, transparency, enforcement, and a focus on the outcomes of poor construction are likely to have a larger impact than voluminous but poorly enforced regulation of the construction process. Where government is the client, attempts to counter corruption need to begin at the level of planning and budgeting. Output-based and community-driven approaches show some promise as tools to reduce corruption. At the same time they will need to be complimented by a range of other interventions including publication of procurement documents, independent and community oversight, physical audit, and public-private anticorruption partnerships.